Muhammad Quraish Shihab’s Methodology in Interpretation of The Qur'an - Aiyub, Aiyub; Mutia, Isna (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
One of Prof. Dr. Muhammad Quraish Shihab's books on archipelago interpretation is titled Tafsir al-Misbah and was authored in Indonesian. It took almost four years to complete, from 1999 to 2002. This interpretation book has added a treasure of interpretation in the Archipelago. It needs to be examined because its author is an expert on interpretation in Indonesia. Besides, he is one of the contemporary scholars. Therefore, this study examines the author’s personality of al-Misbah interpretation book and examines its methodology in interpreting Qur’an, whether he uses the methodology of al-Ma'thur, al-Ra'y or al-Isyari in terms of sources the reference, or he uses the tahlili, al-muqarrin, al-Ijmali and al-Maudhu'i methods in terms of delivery. This article also seeks to ascertain the author's preferred method of interpretation, such as al-Fiqhi, al-adab al-Lughawi, al-adab al-Ijtima'i, etc. This study, which employs library technique, discovers that the al-Ma'thur and al-ra'yi methods, which are excellent for referencing, are used in this commentary book, whereas the tahlili method is used for delivery. It leans toward the interpretation of al-Adab al-Ijtima'i. This interpretation excels in discussing both language and the munasabah (appropriateness of the arrangement) of verses and surahs in the Qur'an.